Postnatal Growth Faltering: Growth and Height Improvement at Two Years in Children with Very Low Birth Weight between 2002–2017 - Lara González-García; Laura Mantecón-Fernández; Marta Suárez-Rodríguez; Rosa Arias-Llorente; Sonia Lareu-Vidal; Aleida Ibáñez-Fernández; María Caunedo-Jiménez; Clara González-López; Eva Fernández-Morán; Belén Fernández-Colomer; Gonzalo Solís-Sánchez (Children, 2022)
The prevalence of postnatal growth faltering (PGF) in preterm infants with very low birth weight (VLBW) (<1500 g) is a universal problem. Growth improvement is expected as neonatal care is optimized. Objectives: To determine if there has been a decrease in the prevalence of PGF and an improvement in height at 2 years in appropriate for gestational age VLBW children in the last two decades. Methods: Clinical descriptive retrospective analysis of neonatal somatometry at birth and at two-year corrected age in VLBW preterm infants. Small for gestational age were excluded. Two cohorts (2002–2006, n = 112; and 2013–2017, n = 92) were compared. Results. In the second five-year period, a decrease in prevalence of PGF was observed (36.6% vs. 22.8%, p = 0.033), an increase in growth rate in the first 28 days (5.22 (4.35–6.09) g/kg/day vs. 11.38 (10.61–12.15) g/kg/day, p < 0.0001) and an increase in height standard deviation (SD) at 2 years (−1.12 (−1.35–−0.91) vs. −0.74 (−0.99–−0.49) p = 0.023). Probability of short stature at 2 years was directly related to daily weight gain in the first 28 days. Conclusions: when comparing two five-year periods in the last two decades, growth in VLBW preterm infants has improved, both during neonatal period and at two years of age.